Education, Poverty, and Unemployment: A Way Forward to Promote Sustainable Economic Growth in Pakistan - Shaheen, Ruqia; Yasmin, Najma; Safdar, Noreen; Yasmin, Fouzia; Khatoon, Sabila (The journal of contemporary issues in business and government, 2021)
Research at hand used a generalized method of moments (GMM) to examine the relationship between economic growth, education, poverty, and unemployment in Pakistan. The study has looked at four different ways to analyzed and compared them with the growth path of Pakistan for the period under study 1990-2020 by providing the integrated approach. This research concluded that education hasan impact on unemployment and poverty, and all have an impact on economic growth in the long run. It shows that there isa fundamentalassociation betweenthe gross domestic product (GDP) and poverty (POV) and amongEducation enrollment. The findings of the research confirmed the positive effect of Education, Trade on economic growth, and unemployment have a negative influence on determining economic growth. This study is of particular concentration topolicymakers as it helps to formulate comprehensive economic policies to support economic development.